Hospitalitas sebagai Imajinasi Etis: Kontribusi Perjanjian Lama bagi Filsafat Pendidikan Anak Usia Dini - Bimo Setyo Utomo (Real Kiddos: Jurnal Pendidikan Anak Usia Dini, 2026)
The instrumentalist tendency in early childhood education which positions academic achievement as the primary goal, has displaced the relational dimension as the foundational basis of human formation. The absence of a philosophical framework capable of restoring education to its relational orientation represents a pressing concern, particularly at the most critical phase of child development. This study aims to reconstruct hospitality as an ethical imagination in the Old Testament and to articulate its contribution to the philosophy of early childhood education. A qualitative approach with a library research design was employed, utilizing philosophical-theological analysis of selected biblical texts (Genesis 18; Exodus 22:21; Leviticus 19:33–34; Deuteronomy 10:18–19) and normative conceptual reconstruction. The findings reveal that hospitality in the Old Testament is not merely a social virtue but an ethical imagination that shapes the moral orientation of the community through three core structures: openness to alterity, an ethics grounded in collective memory, and solidarity that transcends group boundaries. The philosophical reconstruction affirms that hospitality constitutes an educational foundation in which pedagogical action begins with receiving the child as a subject of alterity, education is understood as a practice of welcoming, and relationality is positioned as the pedagogical basis. This study contributes to the development of a relationally grounded philosophy of education by bringing Old Testament biblical ethics into dialogue with contemporary pedagogical reflection, while simultaneously offering a critique of performance-oriented educational paradigms. Keywords: biblical ethics; early childhood education; ethical imagination; hospitality; relationality Abstrak Kecenderungan instrumentalisme dalam pendidikan anak usia dini yang menempatkan capaian akademik sebagai tujuan utama telah menggeser dimensi relasional sebagai fondasi pembentukan manusia. Kekosongan kerangka filosofis yang mampu mengembalikan pendidikan pada orientasi relasionalnya menjadi persoalan mendesak, khususnya pada fase perkembangan anak yang paling krusial. Penelitian ini bertujuan merekonstruksi hospitalitas sebagai imajinasi etis dalam Perjanjian Lama serta merumuskan kontribusinya bagi filsafat pendidikan anak usia dini. Pendekatan kualitatif dengan desain studi kepustakaan digunakan, melalui analisis filosofis-teologis terhadap teks-teks biblika (Kejadian 18; Keluaran 22:21; Imamat 19:33-34; Ulangan 10:18-19) dan rekonstruksi konseptual normatif. Hasil penelitian menunjukkan bahwa hospitalitas dalam Perjanjian Lama bukan sekadar kebajikan sosial, melainkan imajinasi etis yang membentuk orientasi moral komunitas melalui tiga struktur utama: keterbukaan terhadap alteritas, etika berbasis memori kolektif, dan solidaritas melampaui batas kelompok. Rekonstruksi filosofis menegaskan bahwa hospitalitas merupakan landasan konstitutif pendidikan, di mana tindakan pedagogis dimulai dari penerimaan anak sebagai subjek alteritas, pendidikan dipahami sebagai praktik menyambut, dan rasionalitas ditempatkan sebagai fondasi pedagogis. Studi ini berkontribusi pada pengembangan filsafat pendidikan berbasis relasional dengan mempertemukan etika biblika Perjanjian Lama dan refleksi pedagogis kontemporer, sekaligus menawarkan kritik terhadap paradigma pendidikan yang terlalu berorientasi pada peforma. Kata Kunci: etika biblika, hospitalitas; imajinasi etis; pendidikan anak usia dini; relasionalitas